Pengaruh Metode Eksperimen dalam Meningkatkan Hasil Belajar IPA pada Materi Tumbuhan Hijau : The Influence of Experimental Methods in Improving Science Learning Outcomes on Green Plant Material - Danis, Amir; Ayu Lestari, Kartika (ITScience (Information Technology and Science), 2024)
Many students need help understanding the concept of green plants, with low daily test scores and learning motivation. Monotonous and less interactive learning methods bored students, while their practical skills could be improved due to the lack of experimental activities. The quality of science learning also needs to be improved because teachers still need to implement effective, innovative methods. This study aims to assess the learning outcomes of green plant material in fifth-grade students and test the impact of the experimental method on improving these results. The research design used was a one-group pretest-posttest model with 30 students taught using the experimental method. Data were collected through pretest and posttest tests to measure students' understanding before and after applying the experimental method. The results showed that the average student learning outcome before the application of the experimental method was 51.33, while after the application, it increased to 71.33. Hypothesis testing showed that the experimental method positively and significantly affected student learning outcomes, with a t-count value more significant than the t-table (3.571> 2.001). Therefore, the experimental method improves student learning outcomes on green plant material.